Efektivitas Terapi Relaksasi Hand Massage Dalam Mengurangi Kecemasan Pra-Operasi Pada Pasien Kistektomi: Studi Kasus - Agni Cahya Pratiwi; Sri Sumaryani; Eny Hernani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: A study showed that 23.99% of patients experienced severe preoperative anxiety and had adverse effects such as increased blood pressure, contraction of arteries, tachycardia, decreased pressure in some tissues which stimulates the sympathetic nervous system which will affect the healing process, so treatment is necessary pharmacologically and non-pharmacologically. Hand massage is a non-pharmacological way to reduce anxiety. Objective: To measure the effect of hand massage relaxation therapy on anxiety levels in pre-cystectomy patients. Method: This research is a case study with nursing intervention carried out, namely hand massage relaxation therapy on the level of anxiety in Mrs. R pre-operative cystectomy patients for 3 days with a massage duration of 15 minutes and evaluation of anxiety scores using the HARS assessment. Results: The results of this study showed that there was a decrease in anxiety levels using the HARS score from scale 18 with mild anxiety on the first day and scale 7 with no anxiety on the third day. A decrease in the HARS score of 11 indicates that hand massage therapy is effective in reducing anxiety in pre-operative patients. Conclusion: These findings indicate that hand massage therapy can be an effective intervention to reduce pre-operative patient anxiety.